Antistatic resin composition, and packaging material and container each obtained by using the same
The antistatic resin composition, featuring specific antistatic polymer compounds and alkali metal salts or ionic liquids, addresses the limitations of conventional antistatic agents by providing sustained antistatic properties and transparency, thus enhancing the protection and visibility of electronic components.
Patent Information
- Application Number
- JP2023145114
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
Conventional polymeric antistatic agents used in packaging materials for electronic components lack sufficient antistatic properties and transparency, making them unsuitable for effectively preventing static electricity and ensuring the visibility of components.
The development of an antistatic resin composition that incorporates specific antistatic polymer compounds and alkali metal salts or ionic liquids, which are blended with polyolefin resins to create a formulation that provides both long-lasting antistatic properties and high transparency.
The antistatic resin composition effectively prevents static electricity and maintains transparency, ensuring the quality and integrity of electronic components during storage and transportation.
Smart Images

Figure 2025038479000001 
Figure 2025038479000002 
Figure 2025038479000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antistatic resin composition (hereinafter also simply referred to as "resin composition") and a packaging material and a container using the same, and more particularly to an antistatic resin composition which has sufficient, long-lasting antistatic properties and excellent transparency when molded, and is suitable for packaging materials and containers for storing and transporting electronic components, and a packaging material and a container using the same. [Background technology]
[0002] Electrical and electronic equipment uses electronic components such as silicon wafers, hard disks, disk substrates, glass substrates, IC chips, semiconductors, optical storage disks, color filters, hard disk magnetic head elements, CCD elements, etc. When assembling these electrical and electronic equipment, the parts need to be transported and transferred to be fed to the assembly line, and transport containers and packaging materials are used for this purpose. In addition, when parts are stored as intermediate products or finished products, storage containers and packaging materials are used.
[0003] 2. Description of the Related Art Conventionally, synthetic resins such as polyolefin resins, which have excellent moldability and chemical resistance, have been used for containers for transporting and storing electronic components, and packaging materials for packaging electric and electronic components. In such electronic components, the generation of static electricity is a major problem, as it can cause breakdowns and attract fine dust. Therefore, in order to prevent the generation of static electricity, antistatic agents are added to synthetic resins to impart antistatic properties. As such antistatic agents, the use of polymer-type antistatic agents has been proposed to impart long-lasting antistatic properties (e.g., Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-143031 A [Patent Document 2] JP 2011-105330 A [Patent Document 3] JP 2012-62067 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional polymer-type antistatic agents did not have sufficient antistatic properties and their durability. In addition, packaging materials for electronic components may require transparency so that the shape and state of the electronic components inside, as well as information such as bar codes attached to manage the electronic components, can be confirmed. However, when conventional polymer-type antistatic agents are used, there is a problem that sufficient transparency cannot be obtained. Therefore, today, there is a demand for resin compositions that have sufficient and durable antistatic properties and excellent transparency of molded bodies.
[0006] Therefore, an object of the present invention is to provide an antistatic resin composition which has sufficient, long-lasting antistatic properties and excellent transparency when molded, and which is suitable for use as packaging materials and containers for storing and transporting electronic components, and to provide packaging materials and containers using the same. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by combining, in a predetermined ratio, one or more antistatic polymeric compounds having a specific structure with one or more compounds selected from the group consisting of alkali metal salts and ionic liquids, and have thus completed the present invention.
[0008] That is, the antistatic resin composition of the present invention is an antistatic resin composition containing 8 to 50 parts by mass of the following component (X) and 0.4 to 8.0 parts by mass of the following component (Y) per 100 parts by mass of a polyolefin resin. Component (X): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).
[0009] In the antistatic resin composition of the present invention, the polymer compound (E) is preferably obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.
[0010] In the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.
[0011] Furthermore, in the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a structure in which the block polymer (C) having carboxyl groups at both ends and formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds is bonded to the epoxy compound (D) via an ester bond.
[0012] In the antistatic resin composition of the present invention, the epoxy compound (D) of the polymer compound (E) is preferably polypropylene glycol diglycidyl ether. The packaging material of the present invention is characterized in that it is formed by molding the antistatic resin composition. The packaging material of the present invention is preferably a packaging material for electronic parts. The container of the present invention is characterized in that it is formed by molding the antistatic resin composition. The container of the present invention is preferably a container for electronic parts. Effect of the Invention
[0013] According to the present invention, it is possible to provide an antistatic resin composition suitable for packaging materials and containers for storing and transporting electronic components, which has sufficient antistatic properties with long-lasting properties and has excellent transparency when molded, and a packaging material and container using the same. The packaging material and container of the present invention have excellent antistatic properties and long-lasting properties, are less likely to generate static electricity, are less likely to suffer from surface contamination due to static electricity or a decrease in commercial value due to dust adhesion, and are also excellent in transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present invention will be described in detail. First, the antistatic resin composition of the present invention will be described. The resin composition of the present invention contains 8 to 50 parts by mass of the following component (X) and 0.4 to 8.0 parts by mass of the following component (Y) per 100 parts by mass of a polyolefin resin. Component (X): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).
[0015] First, the polyolefin resin used in the present invention will be described. Examples of polyolefin resins include low-density polyethylene, linear low-density polyethylene, high-density polyethylene, homopolypropylene, random copolymer polypropylene, impact copolymer polypropylene, block copolymer polypropylene, isotactic polypropylene, syndiotactic polypropylene, hemiisotactic polypropylene, polybutene, cycloolefin polymer, stereoblock polypropylene, α-olefin polymers such as poly-3-methyl-1-butene, poly-3-methyl-1-pentene, and poly-4-methyl-1-pentene, block or random copolymers of ethylene-propylene, α-olefin copolymers such as ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-vinyl acetate copolymer, and further polyolefin thermoplastic elastomers, and copolymers of two or more of these may be used. Two or more of these polyolefin resins may be used.
[0016] As the polyolefin resin, polyethylene resins such as low-density polyethylene, linear low-density polyethylene and high-density polyethylene are preferred from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0017] Next, the component (X) used in the present invention will be described. The component (X) of the present invention is an antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2).
[0018] In terms of the antistatic property and its durability, and the transparency of the molded product, the polymer compound (E) related to this antistatic agent is preferably a polymer compound obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.
[0019] Further, in terms of antistatic properties and their durability, and transparency of molded articles, the polymer compound (E) preferably has a structure in which a polyester block (A) composed of a polyester (a) and a polyether block (B) composed of a polyether (b) having hydroxyl groups at both ends are bonded via an ester bond or an ether bond formed by the reaction of a hydroxyl group or a carboxyl group at the end of the polyester (a), a hydroxyl group at the end of the polyether (b), and an epoxy group of an epoxy compound (D) having two or more epoxy groups, or a hydroxyl group formed by the reaction of an epoxy group. Here, the hydroxyl group formed by the reaction of an epoxy group of the epoxy compound (D) is a hydroxyl group formed by the ring-opening reaction of the epoxy group of the epoxy compound (D) with a hydroxyl group or a carboxyl group.
[0020] The polyester block (A) of the polymer compound (E) is composed of a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2). The polyester (a) can be obtained by esterification of the diol (a1) with the dicarboxylic acid (a2).
[0021] The diol (a1) used in the polymer compound (E) according to the present invention includes an aliphatic diol and an aromatic group-containing diol. The diol (a1) may be a mixture of two or more kinds.
[0022] Examples of aliphatic diols include 1,2-ethanediol (ethylene glycol), 1,2-propanediol (propylene glycol), 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2,2-diethyl-1,3-propanediol (3,3-dimethylol pentane), 2-n-butyl-2-ethyl-1,3propanediol (3,3-dimethylol heptane), 3-methyl 1,5-pentanediol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-octadecanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, 1,2-, 1,3- or 1,4-cyclohexanediol, cyclododecanediol, dimer diol, hydrogenated dimer diol, diethylene glycol, dipropylene glycol, triethylene glycol, etc. Among these aliphatic diols, 1,4-cyclohexanedimethanol and hydrogenated bisphenol A are preferred from the viewpoints of antistatic properties and their durability, and transparency of molded products, and 1,4-cyclohexanedimethanol is more preferred. From the viewpoints of antistatic properties and their durability, and transparency of molded articles, it is preferable that the aliphatic diol has hydrophobic properties, and therefore it is not preferable to use polyethylene glycol, which has hydrophilic properties.
[0023] Examples of aromatic group-containing diols include bisphenol A, 1,2-hydroxybenzene, 1,3-hydroxybenzene, 1,4-hydroxybenzene, 1,4-benzenedimethanol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, 1,4-bis(2-hydroxyethoxy)benzene, resorcin, polyhydroxyethyl adduct of mononuclear dihydric phenol compounds such as pyrocatechol, etc. Among these diols having aromatic groups, ethylene oxide adduct of bisphenol A and 1,4-bis(β-hydroxyethoxy)benzene are preferred. In addition, the aromatic diol is preferably hydrophobic in terms of antistatic property and its durability, and transparency of the molded product. Among these diols, 1,4-cyclohexanedimethanol is particularly preferred from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0024] The dicarboxylic acid (a2) used in the polymer compound (E) according to the present invention includes an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid. The dicarboxylic acid (a2) may be a mixture of two or more kinds.
[0025] The aliphatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds. The aliphatic dicarboxylic acid preferably includes an aliphatic dicarboxylic acid having 2 to 20 carbon atoms, and examples thereof include oxalic acid, malonic acid, glutaric acid, methylsuccinic acid, dimethylmalonic acid, 3-methylglutaric acid, ethylsuccinic acid, isopropylmalonic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid (1,10-decanedicarboxylic acid), tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanediacetic acid, 1,3-cyclohexanediacetic acid, 1,2-cyclohexanediacetic acid, 1,1-cyclohexanediacetic acid, dimer acid, maleic acid, and fumaric acid. Among these aliphatic dicarboxylic acids, from the viewpoints of antistatic property and its durability, and transparency of a molded product, dicarboxylic acids having 4 to 12 carbon atoms are more preferred, and adipic acid is even more preferred.
[0026] The aromatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.
[0027] The aromatic dicarboxylic acid is preferably an aromatic dicarboxylic acid having 8 to 20 carbon atoms, such as terephthalic acid, isophthalic acid, phthalic acid, phenylmalonic acid, homophthalic acid, phenylsuccinic acid, β-phenylglutaric acid, α-phenyladipic acid, β-phenyladipic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, naphthalenedicarboxylic acid, sodium 3-sulfoisophthalate, potassium 3-sulfoisophthalate, etc. Among these aromatic dicarboxylic acids, terephthalic acid, isophthalic acid, and phthalic acid (including phthalic anhydride) are preferred, and phthalic acid (including phthalic anhydride) is more preferred, from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0028] As the dicarboxylic acid (a2), it is preferable to use both an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid in combination, and it is particularly preferable to use adipic acid as the aliphatic dicarboxylic acid and phthalic acid (including phthalic anhydride) as the aromatic dicarboxylic acid in combination.
[0029] Next, the polyether (b) having hydroxyl groups at both ends and the polyether block (B) of the polymer compound (E) will be described. The polyether block (B) is composed of the polyether (b) having hydroxyl groups at both ends, and the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of the polytetramethylene glycol (b2) is 10 to 80 mol% based on the total number of moles of the polyethylene glycol (b1) and the polytetramethylene glycol (b2).
[0030] The number average molecular weight of the polyethylene glycol (b1) is calculated from the measured value of the hydroxyl value, and from the viewpoints of antistatic property and its durability, and transparency of a molded article, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and even more preferably 1,800 to 4,000. A method for measuring the hydroxyl value and a method for calculating the number average molecular weight from the hydroxyl value are described below.
[0031] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value
[0032] <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution.
[0033] First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of xylene, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]
[0034] The number average molecular weight of the polytetramethylene glycol (b2) is calculated from the measured hydroxyl value, and from the viewpoints of antistatic property and its durability, and transparency of the molded product, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and even more preferably 1,800 to 4,000.
[0035] The method for measuring the hydroxyl value of polytetramethylene glycol (b2) and the method for calculating the number average molecular weight from the hydroxyl value are the same as the method for measuring the hydroxyl value of polyethylene glycol (a1) and the method for calculating the number average molecular weight from the hydroxyl value.
[0036] The ratio of polyethylene glycol (b1) and polytetramethylene glycol (b2) in the polyether (b) having hydroxyl groups at both ends is 10 to 80 mol % of polytetramethylene glycol (b2) relative to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). From the viewpoints of antistatic property and its durability, and transparency of a molded article, the ratio is preferably 15 to 70 mol %, more preferably 18 to 55 mol %, and even more preferably 20 to 50 mol %.
[0037] Next, the epoxy compound (D) having two or more epoxy groups constituting the polymer compound (E) will be described. The epoxy compound (D) used in the antistatic agent of the present invention is not particularly limited as long as it has two or more epoxy groups, and examples thereof include polyglycidyl ether compounds of mononuclear polyhydric phenol compounds such as hydroquinone, resorcin, pyrocatechol, and phloroglucinol; dihydroxynaphthalene, biphenol, methylene bisphenol (bisphenol F), methylene bis(ortho-cresol), ethylidene bisphenol, isopropylidene bisphenol (bisphenol A), isopropylidene bis(ortho-cresol), tetrabromobisphenol, and the like. Polyglyceryl esters of polynuclear polyhydric phenol compounds such as phenol A, 1,3-bis(4-hydroxycumylbenzene), 1,4-bis(4-hydroxycumylbenzene), 1,1,3-tris(4-hydroxyphenyl)butane, 1,1,2,2-tetra(4-hydroxyphenyl)ethane, thiobisphenol, sulfobisphenol, oxybisphenol, phenol novolac, orthocresol novolac, ethylphenol novolac, butylphenol novolac, octylphenol novolac, resorcinol novolac, and terpene phenol. ether compounds; polyglycidyl ethers of polyhydric alcohols such as ethylene glycol, propylene glycol, butylene glycol, hexanediol, diethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, polyglycol, thiodiglycol, glycerin, trimethylolpropane, pentaerythritol, sorbitol, bisphenol A-ethylene oxide adduct, and dicyclopentadiene dimethanol; maleic acid, fumaric acid, itaconic acid, succinic acid, glutaric acid, suberic acid, adipic acid, Homopolymers or copolymers of glycidyl esters of aliphatic, aromatic or alicyclic polybasic acids, such as azelaic acid, sebacic acid, dimer acid, trimer acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid, hexahydrophthalic acid, endomethylenetetrahydrophthalic acid, and glycidyl methacrylate; epoxy compounds having a glycidylamino group, such as N,N-diglycidylaniline, bis(4-(N-methyl-N-glycidylamino)phenyl)methane, and diglycidyl orthotoluidine;Examples of epoxy compounds include cyclic olefin compounds such as vinylcyclohexene diepoxide, dicyclopentadiene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6-methylcyclohexane carboxylate, and bis(3,4-epoxy-6-methylcyclohexylmethyl) adipate; epoxidized conjugated diene polymers such as epoxidized polybutadiene and epoxidized styrene-butadiene copolymers, heterocyclic compounds such as triglycidyl isocyanurate, and epoxidized soybean oil. These epoxy compounds may be internally crosslinked with a prepolymer of terminal isocyanate, or may be polymerized using a polyvalent active hydrogen compound (polyhydric phenol, polyamine, carbonyl group-containing compound, polyphosphate ester, etc.). Two or more of such epoxy compounds (D) may be used.;
[0038] From the viewpoints of antistatic property and its durability, and transparency of a molded article, the epoxy compound (D) is preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, dicyclopentadiene dimethanol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, or hexanediol diglycidyl ether, more preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, or hydrogenated bisphenol A diglycidyl ether, and even more preferably polypropylene glycol diglycidyl ether. From the viewpoints of antistatic property and its durability, and transparency of a molded article, the polypropylene glycol diglycidyl ether is particularly preferably polypropylene glycol diglycidyl ether represented by the following general formula (1).
[0039] [ka]
[0040] In the general formula (1), n represents a number of 1 to 30. n is preferably an number of 2 to 25, and more preferably an number of 3 to 15, from the viewpoints of antistatic property and its durability, and transparency of a molded product.
[0041] The number average molecular weight of the polypropylene glycol diglycidyl ether is preferably from 200 to 2,000, more preferably from 250 to 1,500, and even more preferably from 300 to 1,000, from the viewpoints of antistatic property and its durability, and transparency of a molded product.
[0042] As the polypropylene glycol diglycidyl ether, a commercially available product may be used. Examples of commercially available products include ADEKA GLYCIROL (registered trademark) ED-506 manufactured by ADEKA CORPORATION, DENACOL (registered trademark) EX-920 and DENACOL (registered trademark) EX-931 manufactured by Nagase ChemteX Corporation, and the like.
[0043] The epoxy equivalent of the epoxy compound (D) is preferably from 70 to 2,000, more preferably from 100 to 1,000, particularly preferably from 150 to 600, from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0044] In terms of the antistatic properties and their duration, and the transparency of the molded article, the preferred polymer compound (E) of the present invention is one obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, and has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which a hydroxyl group or a carboxyl group at the end of the polyester (a), a hydroxyl group at the end of the polyether (b), and an epoxy group of an epoxy compound having two or more epoxy groups, or a hydroxyl group formed by the reaction of this epoxy group, are bonded via an ester bond or an ether bond, which is formed by the reaction of these hydroxyl groups or carboxyl groups at the end of the polyester (a),
[0045] Furthermore, from the viewpoints of antistatic properties and their durability, and transparency of molded products, the polymer compound (E) preferably has a structure in which a block polymer (C) having carboxyl groups at both ends, which is formed by repeatedly and alternately bonding a polyester block (A) composed of a polyester (a) and a polyether block (B) composed of a polyether (b) via ester bonds, is bonded to an epoxy compound (D) via an ester bond formed by the carboxyl group of the block polymer (C) and the epoxy group of the epoxy compound (D). It is also preferable that the polymer compound (E) has a structure in which a hydroxyl group formed by ring-opening of the epoxy group in a reaction with the carboxyl group is bonded to the carboxyl group via an ester bond formed by a reaction with the carboxyl group.
[0046] The polyester (a) constituting the block of the polyester (A) according to the present invention may be any one that is composed of a diol (a1) and a dicarboxylic acid (a2), and preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol (a1) and the residue obtained by removing the carboxyl group of the dicarboxylic acid (a2) are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the transparency of the molded article. A more preferred polyester (a) constituting the block (A) of the polyester according to the present invention is one that is composed of a diol, an aliphatic dicarboxylic acid, and an aromatic dicarboxylic acid, and preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aliphatic dicarboxylic acid are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the transparency of the molded article, and further preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aromatic dicarboxylic acid are bonded via an ester bond from the viewpoints of antistatic properties and their duration and the transparency of the molded article.
[0047] From the viewpoints of antistatic property and its durability, and transparency of a molded product, the polyester (a) preferably has a structure having carboxyl groups at both ends. Furthermore, from the viewpoints of antistatic property and its durability, and transparency of a molded product, the polymerization degree of the polyester (a) is preferably in the range of 2 to 50.
[0048] The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above diol (a1) with the above dicarboxylic acid (a2) (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid). The aliphatic dicarboxylic acid may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a derivative is used to obtain polyester (a), both ends may be finally treated to give carboxyl groups, or the polyester may be directly subjected to the next reaction to obtain block polymer (C) having a structure having carboxyl groups at both ends. The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.
[0049] The aromatic dicarboxylic acid may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a polyester is obtained using a derivative, both ends are finally treated to form carboxyl groups, and the polyester may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends. The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.
[0050] When an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid are used, the molar ratio of the residue of the aliphatic dicarboxylic acid excluding the carboxyl group to the residue of the aromatic dicarboxylic acid excluding the carboxyl group in the polyester (a) is preferably 90:10 to 99.9:0.1, more preferably 93:7 to 99.9:0.1, from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0051] The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above-mentioned dicarboxylic acid or its derivative (preferably the above-mentioned aliphatic dicarboxylic acid or its derivative, and the above-mentioned aromatic dicarboxylic acid or its derivative) with the above-mentioned diol.
[0052] Regarding the reaction ratio of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) to diol, it is preferable to use an excess of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) so that both ends have carboxyl groups, and it is preferable to use one mole excess relative to the diol in terms of molar ratio.
[0053] The compounding ratio of the aliphatic dicarboxylic acid or its derivative to the aromatic dicarboxylic acid or its derivative during the esterification reaction is preferably from 90:10 to 99.9:0.1, more preferably from 93:7 to 99.9:0.1, in terms of molar ratio. Depending on the blend ratio and reaction conditions, it may be possible to produce a copolymer consisting of only diols and aliphatic dicarboxylic acids.
[0054] In some cases, a polyester consisting of a diol or an aromatic dicarboxylic acid may be produced. In the present invention, however, the polyester (a) may contain such a polyester, and the polyester (a) may be reacted with the compound (b) as it is to obtain the block polymer (C).
[0055] The esterification reaction may be carried out in the presence of a catalyst for accelerating the reaction. As the catalyst, a conventional catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. may be used.
[0056] In addition, when a derivative of a dicarboxylic acid (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid) such as a carboxylate, a carboxylate metal salt, or a carboxylate halide is used instead of a dicarboxylic acid, the dicarboxylic acid may be reacted with a diol and then treated at both ends to give a dicarboxylic acid, or the dicarboxylic acid may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends.
[0057] A suitable polyester (a) consisting of a diol and a dicarboxylic acid (preferably an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid) and having carboxyl groups at both ends may be any polyester that reacts with a polyether (b) to form an ester bond and form a block polymer (C) structure, and the carboxyl groups at both ends may be protected or modified, or may be in the form of a precursor. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.
[0058] The polyether (b) having hydroxyl groups at both ends preferably reacts with the polyester (a) to form an ester bond or an ether bond, preferably an ester bond, to form a block polymer (C) structure. The hydroxyl groups at both ends may be protected or modified, or may be in the form of a precursor.
[0059] The block polymer (C) having a structure having carboxyl groups at both ends of the polymer compound (E) according to the present invention has a structure in which the block (A) composed of the above polyester (a) and the block (B) composed of the above polyether (b) are repeatedly and alternately bonded via ester bonds formed by carboxyl groups and hydroxyl groups. An example of such a block polymer (C) is one having a structure represented by the following general formula (2).
[0060] [ka]
[0061] In the general formula (2), (A) represents a block composed of the polyester (a) having carboxyl groups at both ends, (B) represents a block composed of the polyether (b) having hydroxyl groups at both ends, and t represents the number of repeating units, which is preferably a number from 1 to 10 from the viewpoints of antistatic property and its durability, and transparency of a molded product. t is more preferably a number from 1 to 7, and most preferably a number from 1 to 5.
[0062] The block polymer (C) having a structure having carboxyl groups at both ends can be obtained by polycondensation reaction of a polyester (a) having carboxyl groups at both ends and a polyether (b) having hydroxyl groups at both ends. However, it is not necessary to synthesize the block polymer (C) from the polyester (a) and the polyether (b) as long as the block polymer (C) has a structure equivalent to a structure in which the polyester (a) and the polyether (b) are repeatedly and alternately bonded via ester bonds formed by a carboxyl group and a hydroxyl group.
[0063] The reaction ratio of the polyester (a) to the polyether (b) is adjusted so that the amount of the polyester (a) is X+1 moles per mole of the polyether (b), thereby making it possible to preferably obtain a block polymer (C) having carboxyl groups at both ends.
[0064] In the reaction, after completion of the synthesis reaction of the polyester (a), the polyester (a) may not be isolated, but the polyether (b) may be added to the reaction system and reacted as is.
[0065] In the polycondensation reaction, a catalyst for promoting the esterification reaction may be used, and as the catalyst, a conventionally known catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.
[0066] From the viewpoints of antistatic property and its durability, and transparency of a molded article, the polymer compound (E) according to the present invention preferably has a structure in which a block polymer (C) having a structure having carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups are bonded via an ester bond. The ester bond may be either an ester bond formed by the reaction between a carboxyl group at the end of the block polymer (C) and an epoxy group of the epoxy compound (D), or an ester bond formed by the reaction between a hydroxyl group formed by this reaction (a reaction between a carboxyl group and an epoxy group) and a carboxyl group, and it is preferable that both ester bonds are present from the viewpoints of antistatic property and its durability, and transparency of a molded article.
[0067] Moreover, the polymer compound (E) may further contain an ester bond formed between a carboxyl group of the polyester (a) and an epoxy group of the epoxy compound (D).
[0068] Furthermore, the polymer compound (E) may contain an ester bond formed between a carboxyl group of the polyester (a) and a hydroxyl group formed by reaction of an epoxy group of the epoxy compound.
[0069] Furthermore, the polymer compound (E) may further contain an ether bond formed by a hydroxyl group of the polyester (a) or a hydroxyl group of the polyether (b) and an epoxy group of the epoxy compound (D).
[0070] In order to obtain a preferred polymer compound (E), the block polymer (C) and the epoxy compound (D) may be reacted. That is, the carboxyl group of the block polymer (C) may be reacted with the epoxy group of the epoxy compound (D). More preferably, the hydroxyl group formed from the reacted epoxy group may be reacted with the carboxyl group. The number of epoxy groups in the epoxy compound (D) is preferably 0.5 to 5 equivalents, more preferably 0.5 to 1.5 equivalents, of the number of carboxyl groups in the block polymer (C) to be reacted. The reaction may be carried out in various solvents or in a molten state.
[0071] The amount of the epoxy compound (D) having two or more epoxy groups to be reacted is preferably 0.1 to 2.0 equivalents, more preferably 0.2 to 1.5 equivalents, relative to the number of carboxyl groups in the block polymer (C) to be reacted.
[0072] In the reaction, after completion of the synthesis reaction of the block polymer (C), the epoxy compound (D) may be added to the reaction system and reacted as it is without isolating the block polymer (C). In this case, the carboxyl groups of the unreacted polyester (a) used in excess when synthesizing the block polymer (C) may react with some of the epoxy groups of the epoxy compound (D) to form ester bonds.
[0073] A preferred polymer compound (E) according to the present invention does not necessarily have to be synthesized from the block polymer (C) and the epoxy compound (D) as long as it has a structure equivalent to that of a block polymer (C) having a structure with carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups bonded via an ester bond formed between the respective carboxyl groups and epoxy groups. The ester bond formed between a carboxyl group and an epoxy group as referred to here also includes an ester bond formed between a carboxyl group and a hydroxyl group formed from an epoxy group by reacting with the carboxyl group.
[0074] In addition, the polymer compound (E) according to the present invention may be prepared by obtaining a polyester (a) from a diol (a1) and a dicarboxylic acid (a2), and then reacting the polyester (a) with a polyether (b) and / or an epoxy compound (D) without isolating the polyester (a).
[0075] In the polymer compound (E) of the present invention, the number average molecular weight of the polyester (a) constituting the block (A) composed of the polyester (a) is, in terms of polystyrene, preferably 1,000 to 10,000, more preferably 1,500 to 8,000, and even more preferably 2,500 to 7,500, from the viewpoints of antistatic property and its durability, and transparency of a molded product. If the number average molecular weight is less than 1,000, the storage stability may be poor, and if it exceeds 10,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to a long reaction time.
[0076] The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is shown below. <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL
[0077] Furthermore, the number average molecular weight of the block polymer (C) having a structure with carboxyl groups at both ends in the polymer compound (E) is preferably 5,000 to 50,000, more preferably 10,000 to 45,000, in terms of polystyrene, from the viewpoints of antistatic property and its durability, and transparency of the molded product. If the number average molecular weight is less than 5,000, the storage stability may be poor, and if it exceeds 50,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to a long reaction time. The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is as described above.
[0078] In the antistatic resin composition of the present invention, the content of the (X) component is 8 to 50 parts by mass relative to 100 parts by mass of the polyolefin resin. From the viewpoints of antistatic property and its durability, and transparency of the molded product, the content is preferably 10 to 45 parts by mass, and more preferably 17 to 40 parts by mass.
[0079] Next, the component (Y) of the present invention will be described. The component (Y) of the present invention is one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).
[0080] Hereinafter, the alkali metal salt (F) will be described first. Examples of the alkali metal salt (F) include salts of organic acids or inorganic acids, and examples of the alkali metal include lithium, sodium, potassium, cesium, and rubidium. Examples of the organic acid include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of the inorganic acid include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid. Among them, in terms of antistatic property and its duration, transparency of the molded product, and safety to living organisms and the environment, lithium, sodium, and potassium salts are preferred, and sodium is more preferred. In terms of antistatic property and its duration, and transparency of the molded product, acetic acid salts, perchloric acid salts, p-toluenesulfonic acid salts, and dodecylbenzenesulfonic acid salts are preferred, and dodecylbenzenesulfonic acid salts are more preferred. Two or more kinds of alkali metal salts may be used.
[0081] Specific examples of the alkali metal salt (F) include lithium acetate, sodium acetate, potassium acetate, lithium chloride, sodium chloride, potassium chloride, lithium phosphate, sodium phosphate, potassium phosphate, lithium sulfate, sodium sulfate, lithium perchlorate, sodium perchlorate, potassium perchlorate, lithium p-toluenesulfonate, sodium p-toluenesulfonate, potassium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, etc. Among these, from the viewpoints of antistatic property and its durability, transparency of the molded product, and safety to living bodies and the environment, preferred are lithium p-toluenesulfonate, sodium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, etc., and most preferred is sodium dodecylbenzenesulfonate.
[0082] Next, the ionic liquid (G) will be described. Examples of ionic liquids include room-temperature molten salts having a melting point of 100°C or less, at least one of the cations or anions constituting the ionic liquid being an organic ion, and having an initial conductivity of 1 to 200 ms / cm, preferably 10 to 200 ms / cm, such as those described in WO 95 / 15572.
[0083] Examples of the cations constituting the ionic liquid include cations selected from the group consisting of amidinium, pyridinium, pyrazolium and guanidinium cations. Among these, examples of the amidinium cation include the following:
[0084] (1) Imidazolinium cation Examples of the imidazolinium include those having 5 to 15 carbon atoms, such as 1,2,3,4-tetramethylimidazolinium and 1,3-dimethylimidazolinium; (2) Imidazolium cation Examples of the imidazolium derivatives include those having 5 to 15 carbon atoms, such as 1,3-dimethylimidazolium and 1-ethyl-3-methylimidazolium; (3) Tetrahydropyrimidinium cation Examples of the aryl group include those having 6 to 15 carbon atoms, such as 1,3-dimethyl-1,4,5,6-tetrahydropyrimidinium and 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium; (4) Dihydropyrimidinium cation Examples of the alkyl group include those having 6 to 20 carbon atoms, such as 1,3-dimethyl-1,4-dihydropyrimidinium, 1,3-dimethyl-1,6-dihydropyrimidinium, 8-methyl-1,8-diazabicyclo[5,4,0]-7,9-undecadienium, and 8-methyl-1,8-diazabicyclo[5,4,0]-7,10-undecadienium.
[0085] The pyridinium cation may be one having 6 to 20 carbon atoms, such as 3-methyl-1-propylpyridinium and 1-butyl-3,4-dimethylpyridinium. The pyrazolium cation may be one having 5 to 15 carbon atoms, such as 1,2-dimethylpyrazolium or 1-n-butyl-2-methylpyrazolium.
[0086] The guanidinium cations include the following: (1) Guanidinium cation with an imidazolinium skeleton Examples of the imidazolium salt include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolinium and 2-diethylamino-1,3,4-trimethylimidazolinium; (2) Guanidinium cation with an imidazolium skeleton Examples of the imidazolium derivatives include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolium and 2-diethylamino-1,3,4-trimethylimidazolium; (3) Guanidinium cation having a tetrahydropyrimidinium skeleton Examples of the alkyl group include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4,5,6-tetrahydropyrimidinium and 2-diethylamino-1,3-dimethyl-4-ethyl-1,4,5,6-tetrahydropyrimidinium; (4) Guanidinium cation having a dihydropyrimidinium skeleton Examples thereof include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4-dihydropyrimidinium, 2-dimethylamino-1,3,4-trimethyl-1,6-dihydropyrimidinium, 2-diethylamino-1,3-dimethyl-4-ethyl-1,4-dihydropyrimidinium, and 2-diethylamino-1,3-dimethyl-4-ethyl-1,6-dihydropyrimidinium.
[0087] The above cations may be used alone or in combination of two or more. Among these, from the viewpoints of antistatic property and its durability, and transparency of a molded product, the amidinium cation is preferred, the imidazolium cation is more preferred, and the 1-ethyl-3-methylimidazolium cation is particularly preferred.
[0088] In the ionic liquid, examples of organic or inorganic acids constituting the anion include the following. Examples of organic acids include carboxylic acids, sulfuric esters, sulfonic acids, and phosphoric esters; examples of inorganic acids include superacids (e.g., borofluoroacid, tetrafluoroboric acid, perchloric acid, hexafluorophosphoric acid, hexafluoroantimonic acid, and hexafluoroarsenic acid), phosphoric acid, and boric acid. The above organic acids and inorganic acids may be used alone or in combination of two or more.
[0089] Among the above organic acids and inorganic acids, those preferred in terms of the antistatic properties and their durability of antistatic properties of ionic liquids and the transparency of molded products are those having an anion constituting the ionic liquid with a Hammett acidity function (-H 0 ) is 12 to 100, conjugate bases of superacids, acids that form anions other than the conjugate bases of superacids, and mixtures thereof.
[0090] Examples of anions other than the conjugate base of a superacid include halogen (e.g., fluorine, chlorine, and bromine) ions, alkyl (having 1 to 12 carbon atoms) benzenesulfonic acid (e.g., p-toluenesulfonic acid and dodecylbenzenesulfonic acid) ions, and poly(n=1 to 25) fluoroalkanesulfonic acid (e.g., undecafluoropentanesulfonic acid) ions.
[0091] In addition, examples of the super strong acid include protonic acids and those derived from a combination of a protonic acid and a Lewis acid, and mixtures thereof. Examples of the protonic acid as the super strong acid include bis(trifluoromethylsulfonyl)imide acid, bis(pentafluoroethylsulfonyl)imide acid, tris(trifluoromethylsulfonyl)methane, perchloric acid, fluorosulfonic acid, alkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., methanesulfonic acid, dodecanesulfonic acid, etc.), poly(n=1 to 30)fluoroalkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoropropanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, and tridecafluorohexanesulfonic acid), borofluoric acid, and tetrafluoroboric acid. Among these, preferred from the viewpoint of ease of synthesis are borofluoroacid, trifluoromethanesulfonic acid, bis(trifluoromethanesulfonyl)imidic acid and bis(pentafluoroethylsulfonyl)imidic acid.
[0092] Examples of protonic acids used in combination with the Lewis acid include hydrogen halides (e.g., hydrogen fluoride, hydrogen chloride, hydrogen bromide, and hydrogen iodide), perchloric acid, fluorosulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, tridecafluorohexanesulfonic acid, and mixtures thereof. Among these, hydrogen fluoride is preferred from the viewpoint of the initial conductivity of the ionic liquid.
[0093] Examples of Lewis acids include boron trifluoride, phosphorus pentafluoride, antimony pentafluoride, arsenic pentafluoride, tantalum pentafluoride, and mixtures thereof. Among these, boron trifluoride and phosphorus pentafluoride are preferred from the viewpoint of the initial conductivity of the ionic liquid.
[0094] The combination of the protonic acid and the Lewis acid is arbitrary, and examples of super strong acids formed by these combinations include tetrafluoroboric acid, hexafluorophosphoric acid, hexafluorotantalic acid, hexafluoroantimonic acid, hexafluorotantalum sulfonic acid, tetrafluoroboric acid, hexafluorophosphoric acid, chlorotrifluoroboric acid, hexafluoroarsenic acid, and mixtures thereof.
[0095] Of the above anions, from the viewpoint of the antistatic properties of the ionic liquid and their durability, preferred are the conjugate bases of super strong acids (super strong acids made of protonic acids and super strong acids made of a combination of a protonic acid and a Lewis acid), and more preferred are the conjugate bases of super strong acids made of protonic acids and super strong acids made of a protonic acid, boron trifluoride and / or phosphorus pentafluoride.
[0096] Among ionic liquids, from the viewpoints of antistatic properties and their durability, and transparency of molded articles, preferred are ionic liquids having an amidinium cation, more preferred are ionic liquids having a 1-ethyl-3-methylimidazolium cation, and particularly preferred is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0097] In the component (Y) of the present invention, the alkali metal salt (F) and the ionic liquid (G) may be used in combination. In the antistatic resin composition of the present invention, the content of the (Y) component is 0.4 to 8.0 parts by mass relative to 100 parts by mass of the polyolefin resin, and from the viewpoints of antistatic property and its durability, and transparency of the molded product, it is preferably 0.8 to 5.0 parts by mass, and more preferably 1.2 to 4.0 parts by mass. When the (Y) component is blended with the polyolefin resin, it may be blended directly, or the (Y) component may be added to the reaction system during the synthesis reaction of the polymer compound (E) which is the (X) component and then blended.
[0098] The resin composition of the present invention preferably contains a compatibilizer in terms of antistatic properties and their durability, and transparency of the molded product. The compatibilizer may be one or more acid anhydride-modified polyolefins. The acid anhydride-modified polyolefin is a polymer in which an acid anhydride such as maleic anhydride is grafted onto a polyolefin.
[0099] The polyolefin portion of the acid anhydride modified polyolefin may be a polymer or copolymer of ethylene, propylene, α-olefin or diene, and examples of the α-olefin include 1-butene, 4-methyl-1-pentene, 1-pentene, 1-octene, 1-decene, 1-dodecene, etc., and examples of the diene include butadiene, isoprene, cyclopentadiene, 1,11-dodecadiene, etc. In addition to these, other copolymerization components may be included. More specifically, examples of the polyolefin include polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / propylene / diene terpolymer, ethylene / 1-butene copolymer, ethylene / vinyl acetate copolymer, and mixtures thereof. Among these, from the viewpoints of antistatic properties and their durability, and transparency of molded products, polymerized or copolymerized ethylene, propylene, α-olefins having 4 to 12 carbon atoms, butadiene, and isoprene are preferred, polymerized or copolymerized ethylene, propylene, α-olefins having 4 to 8 carbon atoms, and butadiene are more preferred, and polymerized or copolymerized ethylene, propylene, and butadiene are even more preferred.
[0100] Examples of the acid anhydride include maleic anhydride and itaconic anhydride, with maleic anhydride being preferred from the standpoints of antistatic properties and their durability, and transparency of the molded product.
[0101] The acid anhydride-modified polyolefin is preferably a maleic anhydride-modified polyolefin, more preferably a maleic anhydride-modified polypropylene, from the viewpoints of antistatic property and its durability, and transparency of a molded product. The acid anhydride-modified polyolefin is obtained by a grafting reaction of an acid anhydride such as maleic anhydride to a polyolefin by a conventionally known method, and various commercially available products may be used.
[0102] In the antistatic resin composition of the present invention, the content of the compatibilizer is preferably 0.01 to 30.0 parts by mass, more preferably 0.1 to 20.0 parts by mass, and even more preferably 0.5 to 15.0 parts by mass, relative to 100 parts by mass of the polyolefin resin, from the viewpoints of antistatic property and its durability, and transparency of the molded product.
[0103] The resin composition of the present invention may further contain a salt of a Group 2 element within a range that does not impair the effects of the present invention. Examples of salts of Group 2 elements include salts of organic acids or inorganic acids, and examples of Group 2 elements include beryllium, magnesium, calcium, strontium, barium, etc. Examples of organic acids include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of inorganic acids include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid.
[0104] The resin composition of the present invention may contain a surfactant within a range that does not impair the effects of the present invention. As the surfactant, a nonionic, anionic, cationic or amphoteric surfactant can be used.
[0105] Examples of the nonionic surfactant include polyethylene glycol-type nonionic surfactants such as higher alcohol ethylene oxide adducts, fatty acid ethylene oxide adducts, higher alkylamine ethylene oxide adducts, and polypropylene glycol ethylene oxide adducts; and polyhydric alcohol-type nonionic surfactants such as polyethylene oxide, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol or sorbitan, alkyl ethers of polyhydric alcohols, and fatty amides of alkanolamines.
[0106] Examples of the anionic surfactant include carboxylates such as alkali metal salts of higher fatty acids; sulfates such as higher alcohol sulfates and higher alkyl ether sulfates; sulfonates such as alkylbenzene sulfonates, alkyl sulfonates and paraffin sulfonates; and phosphates such as higher alcohol phosphates.
[0107] Examples of the cationic surfactant include quaternary ammonium salts such as alkyltrimethylammonium salts. Examples of amphoteric surfactants include amino acid type amphoteric surfactants such as higher alkylaminopropionate salts, betaine type amphoteric surfactants such as higher alkyldimethylbetaine and higher alkyldihydroxyethylbetaine, and the like. These can be used alone or in combination of two or more kinds.
[0108] When a surfactant is added, the amount added is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the polyolefin resin.
[0109] Furthermore, the resin composition of the present invention may contain a polymeric antistatic agent. For example, a known polymeric antistatic agent such as polyetheresteramide can be used as the polymeric antistatic agent. For example, a known polyetheresteramide can be used, which is a polyetheresteramide consisting of a polyoxyalkylene adduct of bisphenol A described in JP-A-7-10989. In addition, a block polymer having a repeating structure with 2 to 50 bond units between a polyolefin block and a hydrophilic polymer block can be used, which is an example of the block polymer described in U.S. Pat. No. 6,552,131.
[0110] When a polymer-type antistatic agent is blended, the blending amount is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the polyolefin resin.
[0111] The resin composition of the present invention may contain thermoplastic resins other than the polyolefin resins described above, as long as the effects of the present invention are not impaired. Examples of other thermoplastic resins include halogen-containing resins such as polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, chlorinated polypropylene, polyvinylidene fluoride, chlorinated rubber, vinyl chloride-vinyl acetate copolymer, vinyl chloride-ethylene copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-vinylidene chloride-vinyl acetate terpolymer, vinyl chloride-acrylic acid ester copolymer, vinyl chloride-maleic acid ester copolymer, and vinyl chloride-cyclohexylmaleimide copolymer; petroleum resin, coumarone resin, polystyrene, polyvinyl acetate, acrylic resin, copolymers of styrene and / or α-methylstyrene with other monomers (e.g., maleic anhydride, phenylmaleimide, methyl methacrylate, butadiene, acrylonitrile, etc.) (e.g., AS resin, ABS resin, ACS resin, SBS resin, MBS resin, heat-resistant ABS resin, etc.); polymethyl methacrylate, polyvinyl alcohol, polyvinyl formal, polyvinyl butyral; polyethylene terephthalate, polybutyric acid ester, polyvinyl chloride ... Examples of the polyalkylene terephthalate include polyalkylene terephthalates such as polycyclohexanedimethylene terephthalate and polycyclohexanedimethylene terephthalate, polyalkylene naphthalates such as polyethylene naphthalate and polybutylene naphthalate, and aromatic polyesters such as polytetramethylene terephthalate; degradable aliphatic polyesters such as polyhydroxybutyrate, polycaprolactone, polybutylene succinate, polyethylene succinate, polylactic acid, polymalic acid, polyglycolic acid, polydioxane, and poly(2-oxetanone); polyamides such as polyphenylene oxide, polycaprolactam, and polyhexamethylene adipamide, polycarbonate, polycarbonate / ABS resin, branched polycarbonate, polyacetal, polyphenylene sulfide, polyurethane, cellulose resin, polyimide resin, polysulfone, polyphenylene ether, polyether ketone, polyether ether ketone, and liquid crystal polymer; and thermoplastic resins such as these, and blends thereof. Further examples of the thermoplastic resin include isoprene rubber, butadiene rubber, acrylonitrile-butadiene copolymer rubber, styrene-butadiene copolymer rubber, fluororubber, and silicone rubber.Further, thermoplastic elastomers are also included, examples of which include polystyrene-based thermoplastic elastomers, polyvinyl chloride-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, etc. These thermoplastic resins may be used alone or in combination of two or more kinds. The thermoplastic resins may also be alloyed.
[0112] Furthermore, various additives such as a phenol-based antioxidant, a phosphorus-based antioxidant, a thioether-based antioxidant, a hindered amine-based light stabilizer, and an ultraviolet absorber can be further added to the resin composition of the present invention within a range that does not impair the effects of the present invention, thereby stabilizing the resin composition of the present invention.
[0113] Examples of the phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl (3,5-di-tert-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid amide], 4,4'-thiobis(6-tert-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-butyl-m-cresol, ... 2,2'-ethylidenebis(6-tert-butyl-m-cresol), 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-ethylidenebis(4-sec-butyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, diethyl)-2,4,6-trimethylbenzene, 2-tert-butyl-4-methyl-6-(2-acryloyloxy-3-tert-butyl-5-methylbenzyl)phenol, stearyl (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate methyl]methane, thiodiethylene glycol bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylene bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 〕, bis[3,3-bis(4-hydroxy-3-tert-butylphenyl)butyric acid]glycol ester, bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl]terephthalate, 1,3,5-tris[(3,5-ditert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, triethylene glycol bis[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], etc. The amount of these phenol-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the polyolefin-based resin.
[0114] Examples of phosphorus-based antioxidants include trisnonylphenyl phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, bis(2,4-ditert-butylphenyl)pentaerythritol diphosphite, bis(2,6-ditert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tritert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2- tert-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite, tetrakis(2,4-ditert-butylphenyl) biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-tert-butylphenyl)-2-ethylhexyl phosphite, 2 ,2'-methylenebis(4,6-tert-butylphenyl)-octadecyl phosphite, 2,2'-ethylidenebis(4,6-di-tert-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, phosphite of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-tert-butylphenol, etc. The amount of these phosphorus-based antioxidants to be added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the polyolefin resin.
[0115] Examples of the thioether-based antioxidant include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and pentaerythritol tetra(β-alkylthiopropionic acid) esters. The amount of these thioether-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the polyolefin resin.
[0116] Examples of the hindered amine light stabilizer include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2 ,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-ditert-butyl-4-hydroxyethyl) dibenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-tert-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4 -piperidyl)amino)-s-triazin-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,2,6,Examples of the hindered amine compounds include 6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl)aminoundecane. The amount of these hindered amine-based light stabilizers added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin-based resin.
[0117] Examples of the ultraviolet absorber include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'- 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-tert-octyl-6-(benzotriazolyl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-carboxyphenyl)benzotriazole; phenyl Benzoates such as ricinate, resorcinol monobenzoate, 2,4-ditert-butylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, 2,4-ditert-amylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, hexadecyl-3,5-ditert-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide, 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl and triaryl triazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine. The amount of these ultraviolet absorbers to be added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin resin.
[0118] Furthermore, if necessary, it is preferable to add a known neutralizing agent to neutralize the residual catalyst in the polyolefin resin. Examples of the neutralizing agent include fatty acid metal salts such as calcium stearate, lithium stearate, and sodium stearate, and fatty acid amide compounds such as ethylene bis(stearamide), ethylene bis(12-hydroxystearamide), and stearic acid amide, and these neutralizing agents may be used in combination. Furthermore, the resin composition of the present invention may further contain, as necessary, metal salts of carboxylates such as sodium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, lithium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, aluminum hydroxybis[2,2'methylenebis(4,6-di-tert-butylphenyl)phosphate], sodium benzoate, aluminum 4-tert-butylbenzoate, sodium adipate, and disodium bicyclo[2.2.1]heptane-2,3-dicarboxylate, dibenzylidene sorbitol, bis(methylbenzylidene)sorbitol, bis(3,4-dimethylbenzyl)phosphate, and the like.
[0043] Nucleating agents such as aromatic carboxylic acid metal salts, alicyclic alkyl carboxylic acid metal salts, aluminum p-tert-butylbenzoate, aromatic phosphate metal salts, dibenzylidene sorbitols, and the like may also be blended.
[0119] Furthermore, to the resin composition of the present invention, metal soaps, hydrotalcites, triazine ring-containing compounds, metal hydroxides, phosphate ester-based flame retardants, condensed phosphate ester-based flame retardants, phosphate-based flame retardants, inorganic phosphorus-based flame retardants, (poly)phosphate-based flame retardants, halogen-based flame retardants, silicon-based flame retardants, antimony oxides such as antimony trioxide, inorganic flame retardant assistants, organic flame retardant assistants, anti-drip agents, fillers, pigments, lubricants, foaming agents, and the like may be added, if necessary.
[0120] Examples of the triazine ring-containing compound include melamine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, melamine pyrophosphate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine.
[0121] Examples of the metal hydroxide include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, zinc hydroxide, and Kismer 5A (magnesium hydroxide: manufactured by Kyowa Chemical Industry Co., Ltd.).
[0122] Examples of the phosphate ester-based flame retardants include trimethyl phosphate, triethyl phosphate, tributyl phosphate, tributoxyethyl phosphate, trischloroethyl phosphate, trisdichloropropyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, trixylenyl phosphate, octyl diphenyl phosphate, xylenyl diphenyl phosphate, trisisopropylphenyl phosphate, 2-ethylhexyl diphenyl phosphate, t-butylphenyl diphenyl phosphate, bis-(t-butylphenyl)phenyl phosphate, tris-(t-butylphenyl)phosphate, isopropylphenyl diphenyl phosphate, bis-(isopropylphenyl)diphenyl phosphate, and tris-(isopropylphenyl)phosphate.
[0123] Examples of the condensed phosphate ester flame retardants include 1,3-phenylene bis(diphenyl phosphate), 1,3-phenylene bis(dixylenyl phosphate), bisphenol A bis(diphenyl phosphate), and the like.
[0124] Examples of the (poly)phosphate-based flame retardant include ammonium salts and amine salts of (poly)phosphoric acids, such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, melamine pyrophosphate, and piperazine pyrophosphate.
[0125] Examples of inorganic flame retardant auxiliary agents include inorganic compounds such as titanium oxide, aluminum oxide, magnesium oxide, hydrotalcite, talc, and montmorillonite, and surface-treated products thereof, and various commercially available products such as TIPAQUE R-680 (titanium oxide: manufactured by Ishihara Sangyo Kaisha), Kyowamag 150 (magnesium oxide: manufactured by Kyowa Chemical Industry Co., Ltd.), DHT-4A (hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.), and Alcamizer 4 (zinc-modified hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.) can be used. Examples of organic flame retardant auxiliary agents include pentaerythritol.
[0126] Furthermore, the resin composition of the present invention may contain additives that are usually used in polyolefin resins, such as crosslinking agents, antifogging agents, plate-out inhibitors, surface treatment agents, plasticizers, lubricants, flame retardants, fluorescent agents, antifungal agents, bactericides, foaming agents, metal deactivators, release agents, pigments, processing aids, antioxidants, light stabilizers, etc., as necessary, within the range that does not impair the effects of the present invention.
[0127] The method for producing the resin composition of the present invention is not particularly limited, and it is sufficient to blend one or more polymer compounds (E) as component (X), one or more selected from the group consisting of alkali metal salts (F) and ionic liquids (G) as component (Y), and other optional components with a polyolefin resin, and any method that is commonly used can be used for the blending method. For example, there is a method of dry blending using a blender or Henschel mixer, or a method of melt blending using an extruder, Banbury mixer, kneader, or the like.
[0128] The polymer compound (E) which is the component (X) may be added as it is, or may be added after impregnating it into a carrier as necessary. To impregnate the carrier, it may be heated and mixed as it is, or it may be diluted with an organic solvent as necessary, impregnated into the carrier, and then the solvent may be removed. As such a carrier, a material known as a filler or bulking agent for synthetic resins, or a flame retardant or light stabilizer which is solid at room temperature may be used, and examples thereof include calcium silicate powder, silica powder, talc powder, alumina powder, titanium oxide powder, or a carrier whose surface is chemically modified, and the flame retardants and antioxidants listed above which are solid, etc. Among these carriers, a carrier whose surface is chemically modified is preferred, and a silica powder whose surface is chemically modified is more preferred. These carriers preferably have an average particle size of 0.1 to 100 μm, and more preferably 0.5 to 50 μm.
[0129] Furthermore, as a method for blending the polymer compound (E) as component (X) into the polyolefin resin, the polymer compound (E) may be synthesized and blended while kneading the block polymer (C) and the epoxy compound (D) having two or more epoxy groups into the resin component, and at that time, one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), as component (Y), may be blended simultaneously. Alternatively, the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the resin component may be mixed during molding such as injection molding to obtain a molded product. Furthermore, a masterbatch of the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the polyolefin resin may be produced in advance, and this masterbatch may be blended. Furthermore, the polymer compound (E) and one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) may be mixed in advance and then blended with the polyolefin resin. Alternatively, the polymer compound (E) synthesized by adding one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) during the synthesis reaction may be blended with the polyolefin resin.
[0130] Next, the packaging material and container of the present invention will be described. The packaging material and container of the present invention are formed from the antistatic resin composition of the present invention. By forming the resin composition of the present invention, a resin molded article having antistatic properties can be obtained. The molding method is not particularly limited, and examples thereof include extrusion processing, calendar processing, injection molding, rolling, compression molding, blow molding, and rotational molding, and molded articles of various shapes such as resin plates, sheets, films, bottles, fibers, and irregular shapes can be produced. The molded article obtained from the resin composition of the present invention has excellent antistatic performance and its durability, as well as transparency.
[0131] Among the molded articles obtained from the resin composition of the present invention, films and sheets in particular are suitable for packaging materials and containers because of their excellent antistatic properties, their durability, and their transparency. These films and sheets are less likely to generate static electricity, are less likely to suffer from surface contamination due to static electricity or a decrease in commercial value due to the adhesion of dust, and are also excellent in transparency. Therefore, they are suitable for packaging materials and containers for electronic parts.
[0132] The packaging material and container obtained from the resin composition of the present invention are suitable for storage containers, transport containers, and packaging materials for electronic parts, such as silicon wafers, hard disks, disk substrates, glass substrates, IC chips, semiconductors, optical storage disks, color filters, hard disk magnetic head elements, CCD elements, and other various parts and products, transport containers, storage containers, trays, cases, packaging materials, carrier tapes, and cover tapes for packaging electronic parts, and the like. EXAMPLES
[0133] The present invention will be described in more detail below using examples, but the present invention is not limited to these.
[0134] According to the following production example, the polymer compound (E) which is the component (X) of the present invention was produced. In the following production example, the number average molecular weight of the polyether (b) was calculated by the following <Method of calculating number average molecular weight from hydroxyl value>, and the number average molecular weights of the polyester (a) and the block polymer (C) were calculated by the following <Method of measuring number average molecular weight in terms of polystyrene>. The molecular weight of the polypropylene glycol diglycidyl ether was calculated from the epoxy equivalent.
[0135] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value
[0136] <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution.
[0137] First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of triethyl phosphate, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]
[0138] <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Co., Ltd. Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL
[0139] [Production Example 1] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-1. The number average molecular weight Mn of the obtained polyester (a)-1 was 2931.
[0140] Next, 205 g of the obtained polyester (a)-1, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-1 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-1 having a structure with carboxyl groups at both ends was 22109.
[0141] To 392 g of the obtained block polymer (C)-1 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-1.
[0142] [Production Example 2] 207 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 153 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 32 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 20 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-2 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-2 having a structure with carboxyl groups at both ends was 22302.
[0143] To 429 g of the obtained block polymer (C)-2 having a structure with carboxyl groups at both ends, 3.9 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 434 g of polymer compound (E)-2.
[0144] [Production Example 3] 196 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 96 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 80 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 50 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-3 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-3 having a structure having carboxyl groups at both ends was 21134. To 376 g of the obtained block polymer (C)-3 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 380 g of polymer compound (E)-3.
[0145] [Production Example 4] 209 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 163 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 24 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 15 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.5 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-4 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-4 having a structure with carboxyl groups at both ends was 22485.
[0146] To 396 g of the obtained block polymer (C)-4 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-4.
[0147] [Production Example 5] 189 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 57 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 112 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 70 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-5 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-5 having a structure having carboxyl groups at both ends was 20372.
[0148] To 396 g of the obtained block polymer (C)-5 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-5.
[0149] [Production Example 6] 202 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 2000 as compound (b1)-2 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 2000 as compound (b2)-2 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-6 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-6 having a structure with carboxyl groups at both ends was 12631.
[0150] To 397 g of the obtained block polymer (C)-6 having a structure with carboxyl groups at both ends, 6.3 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 405 g of polymer compound (E)-6.
[0151] [Production Example 7] 200 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 4000 as compound (b1)-3 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 4000 as compound (b2)-3 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-7 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-7 having a structure with carboxyl groups at both ends was 25243.
[0152] To 398 g of the obtained block polymer (C)-7 having a structure with carboxyl groups at both ends, 3.2 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 402 g of polymer compound (E)-7.
[0153] [Production Example 8] A separable flask was charged with 97 g of 1,4-cyclohexanedimethanol, 112 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-2. The number average molecular weight Mn of the obtained polyester (a)-2 was 2053.
[0154] Next, 185 g of the obtained polyester (a)-2, 185 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 51 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.7 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-8 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-8 having a structure with carboxyl groups at both ends was 18,600.
[0155] To 461 g of the obtained block polymer (C)-8 having a structure with carboxyl groups at both ends, 5.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 467 g of polymer compound (E)-8.
[0156] [Production Example 9] A separable flask was charged with 135 g of 1,4-cyclohexanedimethanol, 143 g of adipic acid, 1.5 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-3. The number average molecular weight Mn of the obtained polyester (a)-3 was 5347.
[0157] Next, 244 g of the obtained polyester (a)-3, 94 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 26 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-9 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-9 having a structure with carboxyl groups at both ends was 31773.
[0158] To 401 g of the obtained block polymer (C)-9 having a structure with carboxyl groups at both ends, 2.6 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 404 g of polymer compound (E)-9.
[0159] [Production Example 10] To 401 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 1.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 304, epoxy equivalent 200 g / eq) as epoxy compound (D)-2 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 403 g of polymer compound (E)-10.
[0160] [Production Example 11] To 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 2.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 769, epoxy equivalent 471 g / eq) as epoxy compound (D)-3 was added, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-11.
[0161] [Production Example 12] 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends, obtained in the same manner as in Production Example 1, was charged with 2.1 g of bisphenol F diglycidyl ether (epoxy equivalent: 170 g / eq) as epoxy compound (D)-4, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-12.
[0162] [Production Example 13] A separable flask was charged with 124 g of hydrogenated bisphenol A, 84 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was gradually heated from 170°C to 215°C while undergoing polymerization at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-4. The number average molecular weight Mn of the obtained polyester (a)-4 was 2922.
[0163] Next, 190 g of the obtained polyester (a)-4, 133 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 37 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-10 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-10 having a structure having carboxyl groups at both ends was 21500.
[0164] To 391 g of the obtained block polymer (C)-10 having a structure with carboxyl groups at both ends, 3.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-13.
[0165] [Production Example 14] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-5. The number average molecular weight Mn of the obtained polyester (a)-5 was 2931.
[0166] Next, 206 g of the obtained polyester (a)-5, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of an antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-11 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-11 having a structure having carboxyl groups at both ends was 22109.
[0167] To 392 g of the obtained block polymer (C)-11 having a structure with carboxyl groups at both ends, 4.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-14.
[0168] [Production Example 15] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 123 g of adipic acid, 0.1 g of phthalic anhydride, 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, ADK STAB AO-60, manufactured by ADEKA CORPORATION), 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, and 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the proportion of polytetramethylene glycol (b2) was 25 mol % relative to the total mole number of polyethylene glycol and polytetramethylene glycol), and polymerization was carried out at normal pressure for 4 hours while gradually increasing the temperature from 170° C. to 215° C. 3.5 g of zirconium octylate was added, and polymerization was carried out under reduced pressure for 7 hours while gradually increasing the temperature from 215° C. to 240° C. to obtain a polymer. The number average molecular weight Mn of the obtained polymer was 22,109.
[0169] To 392 g of the obtained polymer, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours to obtain 396 g of polymer compound (E)-15.
[0170] [Examples 1 to 40, Comparative Examples 1 to 8] Using each resin composition blended based on the compounding amount (parts by mass) shown in Tables 1 to 10 below, a test film was obtained according to the test film preparation method shown below. Using the obtained test film, the surface resistivity (SR value) was measured according to the measurement method shown below, and the antistatic property and its durability were evaluated. Furthermore, the haze value and clarity value were measured and evaluated according to the measurement method shown below. Furthermore, a barcode reading test was performed and evaluated according to the test method shown below. The results are also shown in Tables 1 to 10. Moreover, in the same manner as in the examples, the comparative antistatic agent-1 was used in the compounding amount shown in Tables 1 to 10 and was measured and evaluated. The results are also shown in Tables 1 to 10.
[0171] <Method for Preparing Test Film of Linear Low-Density Polyethylene (LLDPE) Resin Composition> Each resin composition was melt-extruded at 180 °C using an extrusion molding machine equipped with a T-die manufactured by Toyo Seiki Seisakusho Co., Ltd. and quenched with a cooling roll at 40 °C to obtain a test film (5 cm × 12 cm × 50 μm).
[0172] <Method for Preparing Test Film of Low-Density Polyethylene (LDPE) Resin Composition> Each resin composition was melt-extruded at 180 °C using an extrusion molding machine equipped with a T-die manufactured by Toyo Seiki Seisakusho Co., Ltd. and quenched with a cooling roll at 40 °C to obtain a test film (5 cm × 12 cm × 50 μm).
[0173] <Method for Measuring Surface Resistivity (SR Value)> The obtained test film was stored immediately after molding under the conditions of a temperature of 25 °C and a humidity of 50% RH. After 1 day and 30 days of storage after molding, the surface resistivity (Ω / sq) was measured under the same atmosphere using a high resistance meter "Hiresta-UX Hiresta (MCP-HT800)" manufactured by Mitsubishi Chemical Analytech Co., Ltd. under the conditions of an applied voltage of 100 V and an applied time of 1 minute. The measurement was performed at 5 points per test film for 5 test films, and the average value was obtained. When the surface resistivity (Ω / sq) is > 1×10 16 Ω / sq, the measurement is impossible and it is regarded as Over Range (OR).
[0174] <Measurement of Haze Value> The Haze value of the test film was measured in accordance with ISO14782. <Measurement of Clarity Value> The Clarity value of the test film was measured using a haze meter "haze-gard i" manufactured by BYK Additives&Instruments.
[0175] <Method for Barcode Reading Test> The obtained test film was placed on a bar code, and a test was conducted to see whether the bar code information could be read accurately through the film. The test was conducted on 10 sheets of film, and the results were evaluated according to the following criteria. ○: The barcode information was read accurately on all 10 pieces of film. ×: There were some films for which the barcode information could not be read correctly.
[0176] [Table 1] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0177] [Table 2]
[0178] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0179] [Table 3]
[0180] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0181] [Table 4]
[0182] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0183] [Table 5]
[0184] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0185] [Table 6]
[0186] *1: LLDPE: C6-LLDPE (linear low density polyethylene, melt flow rate = 2.0g / 10min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0187] [Table 7]
[0188] *1: LLDPE: C6-LLDPE (linear low density polyethylene, melt flow rate = 2.0g / 10min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0189] [Table 8]
[0190] *1: LLDPE: C6-LLDPE (linear low density polyethylene, melt flow rate = 2.0g / 10min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0191] [Table 9]
[0192] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0193] [Table 10]
[0194] *1: LLDPE: C6-LLDPE (linear low-density polyethylene, melt flow rate = 2.0 g / 10 min) *2: LDPE: (Low density polyethylene, melt flow rate = 2.4g / 10min) *3:NaDBS: Sodium dodecylbenzenesulfonate *4: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *5: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *6: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16
[0195] From the above, it is found that the antistatic resin composition of the present invention has sufficient antistatic properties that last, and when molded into a molded article, the molded article has excellent transparency. The antistatic resin composition is suitable for use as a packaging material and a container for electronic parts.
Claims
1. An antistatic resin composition comprising, per 100 parts by mass of a polyolefin resin, 8 to 50 parts by mass of the following component (X) and 0.4 to 8.0 parts by mass of the following component (Y): Component (X): An antistatic agent containing one or more polymeric compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).
2. 2. The antistatic resin composition according to claim 1, wherein the polymer compound (E) is obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.
3. 3. The antistatic resin composition according to claim 2, wherein the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.
4. 4. The antistatic resin composition according to claim 3, wherein the polymer compound (E) has a structure in which a block polymer (C) having carboxyl groups at both ends thereof, which is formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds, and the epoxy compound (D) are bonded via ester bonds.
5. 2. The antistatic resin composition according to claim 1, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.
6. 3. The antistatic resin composition according to claim 2, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.
7. 4. The antistatic resin composition according to claim 3, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.
8. 5. The antistatic resin composition according to claim 4, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.
9. A packaging material obtained by molding the antistatic resin composition according to any one of claims 1 to 8.
10. 10. The packaging material according to claim 9, which is a packaging material for electronic components.
11. A container, which is formed by molding the antistatic resin composition according to any one of claims 1 to 8.
12. 12. The container of claim 11, wherein the container is for an electronic component.
Citation Information
Patent Citations
Antistatic sheet and packaging molding
JP2009143031A
Antistatic packaging material for electronic component
JP2011105330A
Electric and electronic equipment component carrying case
JP2012062067A